The cellular model for Alzheimer's disease research: PC12 cells - Xie, Danni; Deng, Ting; Zhai, Zhenwei; Sun, Tao; Xu, Ying (Frontiers in Molecular Neuroscience, 2023)
Alzheimer's disease (AD) is a common age-related neurodegenerative disease characterized by progressive cognitive decline and irreversible memory impairment. Currently, several studies have failed to fully elucidate AD's cellular and molecular mechanisms. For this purpose, research on related cellular models may propose potential predictive models for the drug development of AD. Therefore, many cells characterized by neuronal properties are widely used to mimic the pathological process of AD, such as PC12, SH-SY5Y, and N2a, especially the PC12 pheochromocytoma cell line. Thus, this review covers the most systematic essay that used PC12 cells to study AD. We depict the cellular source, culture condition, differentiation methods, transfection methods, drugs inducing AD, general approaches (evaluation methods and metrics), and in vitro cellular models used in parallel with PC12 cells.